Analysis of the Profitability Ratio as Empirical Evidence of Financial Performance in PT Bank Central Asia Tbk Listed on the IDX - Nur Alya Amalia; Muh. Sainil Abidin; Totok Adi Prasetyo (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to analyze the financial performance of PT Bank Central Asia Tbk in terms of profitability ratios during the 2022–2025 period. The research method used is a descriptive quantitative approach utilizing secondary data in the form of the company's annual financial reports obtained through the Indonesia Stock Exchange. Profitability measurement is proxied through three main indicators: Return on Assets (ROA), Return on Equity (ROE), and Return on Investment (ROI) based on total productive assets. The analysis results show that during the observation period, PT Bank Central Asia Tbk was able to maintain very strong and stable financial performance. The average ROA value was recorded at 3.50%, which is well above Bank Indonesia's health standards. Meanwhile, effective equity management resulted in a very competitive average ROE of 20.13%, and strategic fund allocation resulted in an average ROI of 3.81%. Overall, this empirical evidence confirms the very high efficiency in the utilization of operational assets and optimization of the capital structure to provide maximum returns for shareholders with prudent risk management.